2003
DOI: 10.1089/153110703321632499
|View full text |Cite
|
Sign up to set email alerts
|

Large Aerial Bursts: An Important Class of Terrestrial Accretionary Events

Abstract: Large aerial bursts similar to the 1908 Tunguska bolide but much larger in magnitude have surely been responsible for many catastrophic events in the history of the Earth. Because aerial bursts produce shallow (or even negligible) craters, their existence is difficult to document in the geological record. Even aerial bursts as small as Tunguska deposit enough energy to melt approximately 1mm of dry soil. Silica-rich glass formed in such melts has the potential to survive in the soil for many Ma, thus a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 43 publications
(71 reference statements)
3
56
0
Order By: Relevance
“…5), suggesting an origin by one of those causes. Lechatelierite is found in material from Meteor Crater (16), Haughton Crater, the Australasian tektite field (17), Dakhleh Oasis (18), and the Libyan Desert Glass Field (17), having been produced from whole-rock melting of quartzite, sandstones, quartz-rich igneous and metamorphic rocks, and/or loess-like materials. The consensus is that melting begins above 1,700°C and proceeds to temperatures >2;200°C, the boiling point of quartz, within a time span of a few seconds depending on the magnitude of the event (26,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), suggesting an origin by one of those causes. Lechatelierite is found in material from Meteor Crater (16), Haughton Crater, the Australasian tektite field (17), Dakhleh Oasis (18), and the Libyan Desert Glass Field (17), having been produced from whole-rock melting of quartzite, sandstones, quartz-rich igneous and metamorphic rocks, and/or loess-like materials. The consensus is that melting begins above 1,700°C and proceeds to temperatures >2;200°C, the boiling point of quartz, within a time span of a few seconds depending on the magnitude of the event (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Lechatelierite cannot be produced volcanically, but can form during lightning strikes as distinctive melt products called fulgurites that typically have unique tubular morphologies (15). It is also common in cratering events, such as Meteor Crater, AZ (16), and Haughton Crater, Canada § , as well as in probable high-temperature aerial bursts that produced melt rocks, such as Australasian tektites (17), Libyan Desert Glass (LDG) (17), Dakhleh Glass (18), and potential, but unconfirmed, melt glass from Tunguska, Siberia (19). Similar lechatelierite-rich material formed in the Trinity nuclear detonation, in which surface materials were drawn up and melted within the plume (20).…”
Section: Manuscript Textmentioning
confidence: 99%
“…Al-Si-rich spherules have been produced under laboratory conditions from the combustion of charcoal at ∼1,600-2,000°C (35). Also, numerous spherules and melt-glass have been produced in atomic explosions (36,37), including the Trinity detonation in New Mexico in 1945, where the airburst produced spherules similar to those from the Tunguska cosmic airburst in 1908 (8,38). More specifically, the Trinity explosion was a surface burst because the aerial fireball intersected the ground.…”
Section: Significancementioning
confidence: 99%
“…Especially the absence of an impact crater unambiguously related to LDG has caused alternative models to the classical impact hypothesis to be explored. Recently, it was proposed that Libyan Desert Glass supposedly formed by radiative melting from lowaltitude airbursts explosions (e.g., Wasson 2003;Svetsov and Wasson 2007;Boslough and Crawford 2008;Shuvalov and Trubetskaya 2008). These authors suggested that the hot jet of a vaporized projectile comes into contact with the Earth's surface where it expands radially at temperatures high enough to melt silicate minerals (e.g., Boslough and Crawford 2008).…”
Section: Formation Of Libyan Desert Glassmentioning
confidence: 99%